Analisis Perbandingan Quality of Service (QOS) Jaringan 4G LTE Provider Digital Kota Tangerang - Muhammad Emir Sadzali (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2022)
The telecommunication access needs is growing rapidly, this is directly proportional to the development of the modern technological which is very high. Tangerang city is the largest city in Banten with a large number of residents so that the need for internet services is quite high, in addition, Covid-19 pandemic encourages everyone to work from home raises awareness of the need for good and fast internet services to help the implementation of work smoothly, therefore it is necessary to test the quality of internet services provided by internet service providers can be considered in the selection of cellular operators for users and recommendations for improving service quality by ISP. Quality of service is the ability of a network to be able to provide good services, parameters include packet loss, throughput, delay and jitter. The research conducted on three digital provider namely By.U, Live on and MPWR. The tests conducted at five different locations and three different times using wireshark. The test results showed that the quality of internet service in fifth area was fairly good condition only that By.U had poor jitter values when streaming in the afternoon Cibodas and MPWR had a smaller throughput average value in Karawaci area.